Development of bio-mulching materials for weed control, soil moisture conservation and insect repellency in system of rice intensification - Umar, Mohammed (2015)
Weed growth is one of the main constrains of System of Rice Intensification (SRI) due to wide planting spacing (25 × 25 cm or more) and alternate wetting and drying (AWD), thereby reducing rice crop yields up to 70% if there is no weed control attempted. Also, evaporation from the available space due to wide planting pattern and transpiration by the weeds in the SRI field reduces the additional water saving which affect the potential of SRI water productivity. This research was designed to develop a bio-mulching material for weed control, soil moisture conservation with the ability to control insects in SRI farming. Two types of soil cover were made in the study namely;SRImat and UMAR-SRImat. SRImat was made using ground rice straw and plastic net,while UMAR-SRImat was made using flaked rice straw and biodegradable adhesive. The first experiment (field work I) was laid out using randomized complete design (RCD) with five treatments [No soil cover (T1), 0.19 mm thickness of commercialized black Plastic (CBP) (T2), 0.57 mm thickness of CBP (T3), 0.95 mm thickness of CBP (T4) and 2.00 mm thickness of SRImat (T5)] and three replications. The transplanting spacing pattern was 25 cm × 25 cm. While the second experiment (field work II) was laid out using randomized complete block design (RCBD) with four treatments [without soil cover (T1), SRImat (T2), UMAR-SRImat without lemon grass extractLGE) (T3) and UMAR-SRImat with LGE (T4)] and three replications. The transplanting spacing pattern was 30 cm × 30 cm. The analysis was conducted using analysis of variance (ANOVA) and T-test. Volumetric moisture content (VMC) was determined at 24 days after transplanting (DAT) in the first experiment, but at 18 and 25 DAT in the second experiment. Weeds were observed and recorded from the treatment plots to determine the weed density (WD), weed density ratio (WDR), weed dry weight (DW), weed dry weight ratio (DWR) (weed control efficiency), and summed dominance ratio at 24 DAT in the first experiment, while in the second Weed growth is one of the main constrains of System of Rice Intensification (SRI) due to wide planting spacing (25 × 25 cm or more) and alternate wetting and drying (AWD), thereby reducing rice crop yields up to 70% if there is no weed control attempted. Also, evaporation from the available space due to wide planting pattern and transpiration by the weeds in the SRI field reduces the additional water saving which affect the potential of SRI water productivity. This research was designed to develop abio-mulching material for weed control, soil moisture conservation with the ability to control insects in SRI farming. Two types of soil cover were made in the study namely;SRImat and UMAR-SRImat. SRImat was made using ground rice straw and plastic net,while UMAR-SRImat was made using flaked rice straw and biodegradable adhesive. The first experiment (field work I) was laid out using randomized complete design (RCD) with five treatments [No soil cover (T1), 0.19 mm thickness of commercialized black Plastic (CBP) (T2), 0.57 mm thickness of CBP (T3), 0.95 mm thickness of CBP (T4) and 2.00 mm thickness of SRImat (T5)] and three replications. The transplanting spacing pattern was 25 cm × 25 cm. While the second experiment (field work II) was laid out using randomized complete block design (RCBD) with four treatments [without soil cover (T1), SRImat (T2), UMAR-SRImat without lemon grass extract (LGE) (T3) and UMAR-SRImat with LGE (T4)] and three replications. The transplanting spacing pattern was 30 cm × 30 cm. The analysis was conducted using analysis of variance (ANOVA) and T-test. Volumetric moisture content (VMC) was determined at 24 days after transplanting (DAT) in the first experiment, but at 18 and 25 DAT in the second experiment. Weeds were observed and recorded from the treatment plots to determine the weed density (WD), weed density ratio (WDR), weed dry weight (DW), weed dry weight ratio (DWR) (weed control efficiency), and summed dominance ratio at 24 DAT in the first experiment, while in the second experiment at 20 and 40 DAT. Growth performance was determined by collecting the number of tillers at 24 DAT in the first experiment, but at 30 and 40 DAT in the second experiment with additional data of plant height per hill at 30 DAT. The insect population were observed and recorded at 10 DAT, 20 DAT, 30 DAT and 40 DAT. experiment at 20 and 40 DAT. Growth performance was determined by collecting the number of tillers at 24 DAT in the first experiment, but at 30 and 40 DAT in the second experiment with additional data of plant height per hill at 30 DAT. The insect population were observed and recorded at 10 DAT, 20 DAT, 30 DAT and 40 DAT. The result of volumetric moisture content showed that both SRImat and UMARSRImat significantly saved water (253.0447a m3/ha and 3100.0a m3/ha respectively) higher than the control treatment. The effectiveness of SRImat on weed control was 98.5% (WCE) at 24 DAT, while the effectiveness of UMAR-SRImat mulched was 100% at 20 DAT and 99.64% at 40 DAT. The least average number of insect at 20 DAT (3.3 No./m2) appeared in the plots treated with Umar-SRImat comprised of LGE. This research revealed that UMAR-SRImat mulch could control weeds up to 40 DAT as recommended in SRI, retained soil moisture, and repelled insect population up to 20 DAT.